Family Support Increases the Hypertension Medication Adherence in the elderly at Public Health Center of Simpang Tiga Pekanbaru - Dinda Nurannisa; Rizka Febtrina; M. Zul 'Irfan; Dendy Kharisna (Science Midwifery, 2022)
The prevalence of hypertension globally affects 22% of the world's population, and 36% of the incidence rate in Southeast Asia as well as in Indonesia continues to increase. Elderly with hypertension require special care and attention, family support is needed to remind them of medication adherence. The purpose of the study was to determine the correlation of family support and hypertension medication adherence in the elderly at Public Health Center of Simpang Tiga Pekanbaru. Desain of this study is descriptive correlation using cross sectional approach. Sample of this study consists of 112 elderly people with hypertension taken by purposive sampling technique. The instruments in his study used a Morisky Medication Adherence Scale (MMAS) questionnaire and a family support questionnaire. The data analysis used is chi-square. The results of the study from good family support were 59 (52.7%) respondents, family support was sufficient as many as 26 (23.2%) respondents, and families were less as many as 27 (24.1%) respondents. Meanwhile, the results of compliance with hypertension drug consumption were 63 (56.3%) respondents and non-compliance with drug consumption as many as 49 (43.8%) respondents. The results of the Chi-Square statistical test obtained a p-value of 0.002 (p<0.05) meaning that there was a significant relationship between the relationship of family support to adherence to hypertension drug consumption in the elderly at the Public Health Center of Simpang Tiga Pekanbaru. The recommendations of this study are expected by families to always provide motivation and accompany the elderly in their control and activities.